STUDY ON NUTRITIOUS SUPPLEMENT FOR PRE-SCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nutrition is the human basic need and prerequisite for healthy life. A proper diet is essential from very early age of life for growth, development and active life style. Nutrition is the science that deals with all the various factors of which food is composed and the way in proper nourishment is brought about. A proper balance of healthy snacks for kids, healthy day care lunch menus, preschool treats and school lunch ideas will make your kids and preschoolers feel great, provide more healthy productive energy as well as to improve their concentration, development and individual dispositions. Your toddler and kids need the proper preschool nutrition from their pre-school snacks, pre-school treat and day care lunch. The biscuit sample prepared with incorporation of higher amount of malted ragi flour was rich in minerals, crude fibre. Addition of bengalgram flour increased protein, fibre, fat and mineral so malting was beneficial. Nutritional addition of bengalgram flour to the biscuits proved to be superior in quality. Sprouted wheat flour makes biscuit much easier for children to digest since much of the sugar was vegetable sugar. The biscuit sample prepared with 45% wheat, 15% ragi, 30% Bengal gram and 5% skim milk powder was good in taste, nutritionally balance & acceptable by the people.